Tracheal reconstructive surgery under ECMO for the treatment of congenital tracheal stenosis in the premature infant: case report - Xu, Qian Ya; Sapana, Tamang; Qi, Yu; Fu, Guo Wei; Guo, Long Hui; Ma, Wei; Wang, Li Li; Zhao, Gai; Wang, Hai Xia; Zhang, Qian (Frontiers in Pediatrics, 2024)
Background Congenital tracheal stenosis (CTS) is a rare but life-threatening malformation of the trachea. Surgical reconstruction is the treatment of choice in symptomatic cases which is highly risky and is rarely performed in extremely premature infants. With this, reporting a case of CTS managed by tracheal reconstructive surgery under ECMO in a baby weighing 1.47 kg at 32 + 1 WOG was the first ever case in China. Case presentation A premature newborn with a very low birth weight (VLBW) was admitted to our institute for breathing difficulties, requiring mechanical ventilation, and experienced two unsuccessful attempts of extubation. The team performed tracheal reconstructive surgery supported by ECMO after identifying lower tracheal stenosis through a bronchoscopy examination. One month after the surgery, oxygen support was able to discontinue. The patient's entire hospitalization was incredibly challenging, marked by hemodynamic instability with persistent anemia, and disseminated intravascular coagulation (DIC), which were managed with great care. Despite the difficult stay, a follow-up bronchoscopy revealed no obstruction or tracheal stenosis, leading to a successful discharge. Conclusion Advancements in diagnostic techniques and innovative management methods have made diagnosing and treating CTS easier, even in premature infants. Our case is the first in China to successfully undergo tracheal reconstructive surgery supported by ECMO, inspiring future achievements in the medical field.